Kontribusi Usaha Mikro, Kecil, dan Menengah (UMKM) dalam Penyerapan Kontribusi Tenaga Kerja di Jawa Barat - Muslihat, Asep; Nurjannah, Fitri (Peneliti.net, 2024)
Micro, Small and Medium Enterprises (MSMEs) are innovations that can be used as a foundational strength for a country, especially Indonesia which is still at the level of a developing country. It is hoped that MSMEs can play an important role in the economy in West Java, considering the history of Indonesia experiencing a monetary crisis in business. Micro, Small and Medium Enterprises (MSMEs) were able to survive and tended to increase at that time, while many large-scale businesses experienced losses and even went bankrupt. This research uses a qualitative descriptive approach, describing the data objectively. This research data is accessed via the BPS website. The problem formulation used in this research is how MSMEs contribute to labor absorption, and what are the opportunities for MSMEs to absorb labor. The results of this research reveal that MSMEs have a dominant role in absorbing labor in West Java. In line with the increase in MSMEs, labor absorption has increased significantly. So Micro, Small and Medium Enterprises play an important role in absorbing labor in West Java. However, there is a need for top level regional entrepreneurs who are experienced in developing groups of methods or breakthroughs that have never existed before in order to be able to compete in the global market.